The effect of assigning dedicated general practitioners to nursing homes. (17th January 2019) - Weatherall, Cecilie Dohlmann; Hansen, Anne Toft; Nicholson, Sean
Abstract : Objective: To determine whether assigning a dedicated general practitioner (GP) to a nursing home reduces hospitalizations and readmissions. Data Sources/Study Setting: Secondary data on hospitalizations and deaths by month for the universe of nursing home residents in Denmark from January 2011 through February 2014. Study Design: In 2012, Denmark initiated a program in seven nursing homes that volunteered to participate. We used a difference‐in‐differences model to estimate the effect of assigning a dedicated GP to a nursing home on the likelihood that a nursing home resident will be hospitalized, will experience a preventable hospitalization, and will be readmitted. The unit of observation is a resident‐month. Data Collection/Extraction Methods: Data were extracted from the Danish public administrative register dataset. Principal Findings: We found that assigning a GP to a nursing home was associated with a 0.55 [95 percent CI, 0.08 to 1.02] percentage point reduction in the monthly probability of a preventable hospitalization, which was a 26 percent reduction from the preintervention level of 2.13 percentage points. The associated reduction in the monthly probability of a readmission was 0.68 [95 percent CI, −0.01 to 1.37] percentage points, which was a 25 percent reduction from the baseline level of 2.68 percentage points. Survey results indicated that the likely mechanism for the effect was more efficient and consistent communication between GPs and nursing home personnel. Conclusions: Assigning a dedicated physician in a nursing home can reduce medical spending and improve patients' health.